2020
DOI: 10.1186/s12872-020-01676-x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-modified citrullinated vimentin antibody: a novel biomarker associated with cardiac systolic dysfunction in patients with rheumatoid arthritis

Abstract: Background: Studies have demonstrated that seropositive patients with rheumatoid arthritis (RA) are susceptible to cardiovascular diseases (CVDs). In this study, we aimed to determine the association of autoantibodies with the echocardiographic parameters of systolic and diastolic dysfunction in such patients. Methods: In this cross-sectional study, we evaluated patients with RA who were referred to our clinic from October 2017 to August 2018. After the exclusion of patients with concomitant CVD, all patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Numerous studies have revealed that RA and SLE can affect HF and other cardiovascular events (see review article References [ 105 ] and [ 106 ]). Furthermore, in RA patients, the plasma levels of ACPA and antimodified citrullinated vimentin antibody (AMCVA) are negatively correlated with LVEF [ 107 ]. Another study showed that higher ACPA and AMCVA levels are associated with higher adjusted mean left ventricular mass index (LVMI) compared with the lower antibody group [ 108 ].…”
Section: Netosis In Diseases Inducing Hfmentioning
confidence: 99%
“…Numerous studies have revealed that RA and SLE can affect HF and other cardiovascular events (see review article References [ 105 ] and [ 106 ]). Furthermore, in RA patients, the plasma levels of ACPA and antimodified citrullinated vimentin antibody (AMCVA) are negatively correlated with LVEF [ 107 ]. Another study showed that higher ACPA and AMCVA levels are associated with higher adjusted mean left ventricular mass index (LVMI) compared with the lower antibody group [ 108 ].…”
Section: Netosis In Diseases Inducing Hfmentioning
confidence: 99%